Analisis Penerapan Elektronik Pajak Bumi dan Bangunan Pedesaan dan Perkotaan (E-PBB P2) - Putri Febriana Wijayanti; Elva Nuraina; Elly Astuti (Akuntansi & Ekonomika, 2021)
This study aims to analyze the application of the Electronic Land and Building Tax in Urban and Rural (E-PBB P2) at the Regional Financial and Asset Management Revenue Agency of Magetan Regency. The research method uses descriptive qualitative. Sources of data used are primary and secondary data sources. Data collection techniques are interviews, observations, and documentation. Data analysis techniques use data reduction, presentation of information data, and concluding. The results of the implementation of E-PBB in Magetan Regency have been maximized from data collection, assessment, determination, billing, payment, and services. Although there are still some obstacles, such as the application network, the system is not optimal and taxpayers' low participation. In terms of income, the increase was not significant. Only the circulation of billed money that went to the Regional Government was faster.